Community perceptions of malaria and malaria treatment behaviour in a rural district of Ghana: implications for artemisinin combination therapy - Boahen Owusu; Adda Robert; Amenga-Etego Seeba; Sulemana Abubakari; Awini Elizabeth; Owusu Ruth; Zandoh Charles; Abokyi Livesy; Asante Kwaku P; Segbaya Sylvester; Mahama Emmanuel; Bart-Plange Constance; et al. (BMC, 2010)
Abstract Background Artesunate-amodiaquine (AS-AQ) was introduced in Ghana as the first line drug for treatment of uncomplicated malaria in 2004. We report the perceptions of malaria and malaria treatment behaviour, the community awareness of and perceptions about AS-AQ two years after the introduction of this ACT treatment for malaria. Methods Two surveys were conducted; a cross-sectional survey of 729 randomly selected household heads (urban-362, rural-367) and 282 women with children < 5 years (urban-121, rural-161) was conducted in 2006. A district wide survey was conducted in 2007 to assess awareness of AS-AQ. These were complemented with twenty-eight focus group discussions (FGDs) and 16 key informant interviews (KII) among community members and major stakeholders in the health care delivery services. All nine (9) health facilities and five (5) purposively selected drug stores were audited in order to identify commonly used anti-malarials in the study area at the time of the survey. Results Majority of respondents ( > 75%) in the sampled survey mentioned mosquito bites as the cause of malaria. Other causes mentioned include environmental factors (e.g. dirty surroundings) and standing in the sun. Close to 60% of the household heads and 40% of the care-givers interviewed did not know about AS-AQ. The community respondents who knew about and had ever taken AS-AQ perceived it to be a good drug; although they mentioned they had experienced some side effects including headaches and body weakness. Co-blistered AS-AQ was available in all the government health facilities in the study area. Different formulations of ACTs were however found in urban chemical shops but not in rural chemical stores where monotherapy antimalarials were predominant. Conclusion The knowledge of fever as a symptom of malaria is high among the study population. The awareness of AS-AQ therapy and its side-effect was low in the study area. Community education and sensitization, targeting all categories of the population, has to be intensified to ensure an efficient implementation process.